1998
DOI: 10.1042/bj3300041
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-binding domains of glycanases from Streptomyces lividans: characterization of a new family of xylan-binding domains

Abstract: The substrate-binding domains of six glycanases from Streptomyces lividans were investigated to determine their specificity towards cellulose and xylan. Based upon amino acid sequence similarities, four of the six domains could be assigned to existing cellulose-binding domain families. However, the binding domains of xylanase A and arabinofuranosidase B could not be classified in any of the known families and should therefore be classified as members of a new family. Evidence is also presented that this new fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
(32 reference statements)
0
36
0
4
Order By: Relevance
“…Tomme et al (1995) divide the CBD II family into CBD IIa and CBD IIb, the latter having a C-terminal deletion covering an otherwise conserved Trp residue. On this criterion, the CBD domains of Hoglet-N are in the CBD IIb subfamily (also called XBD, xylanbinding domains, reflecting binding specificity of some domains; Dupont et al 1998). …”
Section: Resultsmentioning
confidence: 99%
“…Tomme et al (1995) divide the CBD II family into CBD IIa and CBD IIb, the latter having a C-terminal deletion covering an otherwise conserved Trp residue. On this criterion, the CBD domains of Hoglet-N are in the CBD IIb subfamily (also called XBD, xylanbinding domains, reflecting binding specificity of some domains; Dupont et al 1998). …”
Section: Resultsmentioning
confidence: 99%
“…However, this type CBM6 module had highest affinity for xylan, and bound only weakly to Avicel and acid-swollen cellulose. Dupont et al (1998) have shown that the Streptomyces lividans xylanases AxeA and XlnB possess the family 2 of carbohydrate-binding modules, which specifically bind insoluble xylan and do not bind cellulose. The modular structure of xylanase of A. pushchinoensis A8 is a future task of ongoing studies to determine its entire gene sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal region of Xyn5 containing family 22 CBMs (i.e., CBM22-1 and CBM22-2), extending from positions 43 to 365 (numbered from the initial Met of the polypeptide encoded by xyn5), have sequence similarity with the family 22 CBMs of C. josui Xyn10A, Clostridium stercorarium Xyn10B, C. thermocellum Xyn10B, Clostridium fini XynC, Thermotoga maritima Xyn10A, and Thermoanaerobacterium saccharolyticum XynA (i.e., the sequence identities between the family 22 CBMs of Xyn5 and those of the other xylanases are 46.8 to 21.9%). It has been shown that the family 22 CBM of T. maritima Xyn10A and several other family 10 xylanases have the ability to bind soluble xylan (3,8,10,18) and that the family 22 CBMs of T. maritima Xyn10A and T. saccharolyticum XynA contribute to the heat stability of these enzymes (15,18,35). The family 10 catalytic domain of Xyn5, extending from positions 370 to 712 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the cellulose-binding activity, Xyn5 would have xylan-binding activity because of the presence of the family 22 CBMs. It has been shown that family 22 CBMs of T. maritima Xyn10A and C. thermocellum Xyn10B have xylanbinding and thermostabilizing functions (3,8,10,15,18,35 is replaced with another aromatic amino acid, Tyr. In addition, CBM22-2 of Xyn5 has 28.2% amino acid sequence identity with C. thermocellum Xyn10B.…”
Section: Discussionmentioning
confidence: 99%